Congenital duplication of the larynx. Issue 6 (9th June 2014) - Simpson, A I; Khanna, A; Stanton, A
Abstract Introduction: The larynx is an intricate structure serving three important functions in humans: it protects the lower respiratory airway, facilitates respiration and helps produce sound through a key role in phonation. Objective: We report the first published finding of congenital duplication of the larynx in a patient with previously cleared squamous cell carcinoma of the neck and a new diagnosis of squamous cell carcinoma of the lung. Case report: We describe the incidental finding of duplication of the larynx in a 62-year-old man with previously completely cleared squamous cell carcinoma of the neck, who presented with worsening dyspnoea. We also provide a brief overview of other published cases in which duplication of the vocal folds and epiglottis has been reported. Results: Our patient experienced no symptoms related to this incidental finding of congenital duplication of the larynx. Conclusion: The first case of congenital duplication of the larynx is currently of academic interest only; however, the possible association with squamous cell carcinoma is postulated to raise awareness in clinicians who may observe further cases in the future.